UPAYA PENERAPAN MODEL BLENDED-LEARNING UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS DALAM PEMBELAJARAN SEJARAH - Tarunasena (2013)
The thesis is titled "The Attempts of Implementing Blended Learning Model to Improve Critical Thinking Ability in History Teaching and Learning". The issue put forward in this thesis centers on "How Are the Attempts of Implementing Blended Learning Model to Improve Critical Thinking Ability in the Teaching and Learning of History?". This focus was prompted by the researcher's experience and preliminary observations that showed the teaching and learning process using discussion only or assignment through e-learning with essay as the end product without any discussion failed to improve the critical thinking ability of students. The discussion developed tended to merely improve cooperation between students and did not affect the critical thinking ability. The same is true for assignment through e-learning; even though it seemed to be compact, it gave an impression of merely "copy and paste".Consequently, the originality of the assignment is questionable. Therefore, the researcher attempted to find the answers to the following questions: 1) How to plan blended-learning to improve the critical thinking ability in the teaching and learning of History?; 2) How is the conduct of blended learning model in an attempt of improving the critical thinking ability in the teaching and learning of History?; and 3) How to solve problems that emerge in the implementation of blended-learning model to improve the critical thinking ability? This research employed qualitative approach with Classroom Action Research method. The outcomes of the research can be concluded as follows: first, in the planning stage, syllabus, course unit, field notes, observatory checklists, and learning management system (LMS) using moodle software made available by the Directorate of ICT of Indonesia University of Education were all prepared beforehand. In addition to functioning as a tool of evaluation, LMS serves as a tool for observation of e-learning instruction. Second, the implementation of blended learning model was proven to significantly improve the critical thinking ability in the teaching and learning of History through three cycles. Third, the obstacles emerged in this research that were ultimately technical in nature in terms of essay assignment that had to be submitted online could be handled by the use of CD. Meanwhile, for the issue of time allocation, towards the end of the research, it could not be solved. Through this research, the researcher recommends: First, for the Department of History Education, the subject of ICT should be made compulsory, instead of elective. Second, college students should make use of e-learning as one of the alternative of resources and teaching media that will develop their own and their future students' critical thinking. The same is applicable for fellow lecturers; the researcher highly recommends the use of Blended Learning in each subject they teach, because in addition to improving students' critical thinking ability, it can also reduce the dehumanizing process in the internet-based lectures. Third, for other researchers interested in further research, it is suggested that investigation on the weaknesses of this research can be conducted, both the ones the researcher is aware of and the ones he is not. The researcher also recommends that future interested researchers conduct research and development for this Blended Learning model. Tesis ini berjudul "Upaya Penerapan Model Blended Learning Untuk Meningkatkan Kemampuan Berpikir Kritis dalam Pembelajaran Sejarah.". Masalah yang diangkat dalam tesis ini berkaitan tentang "Bagaimana Upaya Penerapan Model Blended Learning Untuk Meningkatkan Kemampuan Berpikir Kritis dalam Pembelajaran Sejarah?". Fokus masalah yang diangkat dalam tesis ini dilatarbelakangi oleh pengalaman peneliti yang berdasarkan hasil observasi awal menunjukkan bahwa proses pembelajaran dengan menggunakan diskusi saja, ataupun penugasan melalui e-learning yang menghasilkan essay saja tanpa didiskusikan, terbukti tidak berhasil meningkatkan kemampuan berpikir kritis peserta didik. Diskusi yang dikembangkan lebih cenderung hanya meningkatkan kerjasama di antara mahasiswa, kurang menyentuh kemampuan berpikir kritis. Demikian juga dengan penugasan melalui e-learning, walaupun apa yang dihasilkan tampak bernas, tapi terkesan "copy and paste". Jadi menimbulkan kesangsian terhadap orisinalitas tugas yang dimaksud. Dengan demikian peneliti berusaha menjawab pertanyaan penelitian berikut ini: 1) Bagaimana merencanakan blended-learning untuk meningkatkan kemampuan berpikir kritis dalam pembelajaran Sejarah? 2) Bagaimana pelaksanaan model blended-learning untuk meningkatkan kemampuan berpikir kritis dalam pembelajaran Sejarah ? 3)Bagaimana mengatasi kendala-kendala yang muncul pada penerapan model blended-learning dalam upaya peningkatan kemampuan berpikir kritis? Penelitian ini menggunakan pendekatan kualitatif dengan metode Penelitian Tindakan Kelas (Classroom Action Research). Hasil penelitian menyimpulkan beberapa hal: pertama pada tahap perencanaan dipersiapkan secara matang silabus, satuan acara perkuliahan, format catatan lapangan, ceklist pengamatan, serta learning management system(LMS) dengan memanfaatkan software moodle yang disediakan Direktorat TIK UPI. LMS selain berfungsi sebagai alat evaluasi juga berfungsi sebagai alat observasi proses pembelajaran melalui e-learning. Kedua, pelaksanaan penerapan model blended learning terbukti secara signifikan dapat meningkatkan kemampuan berpikir kritis dalam pembelajaran sejarah yang dilakukan melalui tiga siklus. , Ketiga,. kendala-kendala yang muncul dalam penelitian ini terutama kendala teknis pada tugas esai yang harus dikumpulkan secara online dapat diatasi dengan menggunakan CD. Sedangkan kendala alokasi waktu, hingga akhir penelitian tidak berhasil diatasi. Melalui penelitian ini, penulis merekomendasikan pertama, bagi pihak jurusan Pendidikan Sejarah agar dapat menjadikan mata kuliah TIK dalam Pembelajaran Sejarah yang sekarang merupakan mata kuliah pilihan, menjadi mata kuliah wajib. Kedua, bagi mahasiswa sebaiknya pemanfaatan e-learning dapat digunakan sebagai salah satu alternatif sumber dan media pembelajaran yang akan mengembangkan kemampuan berpikir kritis mahasiswa itu sendiri, dan untuk siswa-siswa di sekolah tempat yang bersangkutan mengabdikan diri. Demikian juga untuk dosen-dosen lainnya, peneliti sangat menganjurkan penggunaan Blended Learning ini pada masing-masing perkuliahan yang diampunya, karena selain dapat meningkatkan kemampuan berpikir kritis mahasiswa, juga dapat mereduksi proses dehumanisasi pada perkuliahan berbasis internet. Keempat, bagi peneliti lain yang berminat melakukan penelitian lanjutan, agar dilakukan identifikasi terhadap kelemahan-kelemahan penelitian ini baik yang disadari peneliti maupun yang tidak. Peneliti menganjurkan bagi yang berminat melakukan penelitian lanjutan, agar melakukan penelitian pengembangan (R&D) pada model Blended Learning ini.